Habitat selection by reintroduced guanacos (Lama guanicoe) in a heterogeneous mountain rangeland of central Argentina - Flores, Celina Eliana (2012)
Quebrada del Condorito National Park is located in the upper belt of the mountains of central Argentina and preserves a heterogeneous rangeland area. After the creation of the National Park, in 1996, domestic livestock were gradually removed to avoid soil loss and degradation due to overgrazing in this fragile ecosystem. Lack of large-scale herbivory allowed the expansion of tussock grasslands over grazing lawns. In 2007 a guanaco (Lama guanicoe) population was reintroduced; this large native herbivore, that had become extinct in the region was selected, because it is a low-impact grazer. Habitat selection by the guanaco population reintroduced to the National Park was studied. Seven habitat types previously defined for the region were considered, each one exhibiting a particular dominant plant growth form and different per cent cover of plant species. Guanacos made a positive selection of moist and dry grazing lawns, and avoided tussock grasslands and forests. The reintroduced guanacos selected landscapes with short plants and a high percentage of perennial graminoids and forbs, which are guanacos’ preferred food items. The results indicate that availability of forage of a nutritive value and dominant plant growth form largely explain habitat selection by guanaco in the National Park; this information can be useful for both the ongoing guanaco reintroduction project and the design of management strategies aimed at ecological restoration of this important rangeland region of central Argentina.